Stability of the trivial solution of a one-dimensional mathematical model of thermoelasticity - Orlov, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Lyapunov stability is established for a one-dimensional physically linear mathematical model of thermoelasticity. For this purpose, the convergent iteration process is constructed; it consists of solving hyperbolic and parabolic problems successively by using new estimates for the solution of a mixed problem for the wave equation.